Revitalizing Family Resilience as An Effort to Prepare The Golden Generation in Paudud and TK Citra Insani Betak Village, Kalidawir District, Tulungagung Regency, East Java - Siti Mas'udah; Sri Endah Kinasih; Yuyun Wahyu Izzati Surya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2022)
Children are the next generation of the nation. In the future, the leadership of this nation is in their hands. Therefore, children must be well prepared. The role of parents is very large in socializing children. Therefore, parents' knowledge about childcare must be improved. In this case, the family plays an important role in producing a qualified next generation because at a macro level, the resilience of the nation depends on the resilience of the family. In the future, this nation will be led by the generation that is currently experiencing socialization in the family. Therefore, on a micro level, parents must be empowered because socialization starts from the family. Increasing parents' knowledge is done by making efforts to revitalize family functions in preparing the golden generation.